2019
DOI: 10.2147/vmrr.s189566
|View full text |Cite
|
Sign up to set email alerts
|

<p>Resilience In Dogs? Lessons From Other Species</p>

Abstract: What are the key factors of psychological resilience in dogs? Why do some individuals recover swiftly from neglect, abuse or several years of harsh kennel environments, while some seem to be permanently traumatized by much milder adverse experiences? Resilience is a concept seldom discussed in canine studies; however, many studies have identified risk factors (both environmental and genetic) for developing anxieties, aggression or other behavioral problems. These studies also indicate several factors that may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 92 publications
(168 reference statements)
0
2
0
Order By: Relevance
“…Dogs assessed to have behaviour disorders scored poorer in their response to stressors (resilience) [33] and they encountered stressful stimuli more often than healthy dogs. Similar to dogs displaying aggression, the response to a perceived threat and the time it takes to recover may be influenced by genetics and their experiences as a young dog.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dogs assessed to have behaviour disorders scored poorer in their response to stressors (resilience) [33] and they encountered stressful stimuli more often than healthy dogs. Similar to dogs displaying aggression, the response to a perceived threat and the time it takes to recover may be influenced by genetics and their experiences as a young dog.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there is extremely limited research examining resilience in dogs and the association of social interactions. In humans, engagement in social activity promotes higher levels of emotional stability and resilience [54] and it is suggested that positive interaction with dog caregivers through activities such as play may increase dog resilience and their ability to cope with stress [33]. When dogs have strong and secure attachments to their caregivers, they may develop better coping mechanisms to stressful events [55].…”
Section: Discussionmentioning
confidence: 99%
“…The developing puppy is, however, more vulnerable than an adult dog due to their behavioural immaturity and pliability [34,35] and the absence of resilience [36]. The experiences and behaviour of dogs during their first year of life are crucial in determining their later behaviour and temperament [37]. A maladaptive response to stress during puppyhood, referred to as a toxic stress response [38], plays an important role in the pathway from early adversity to physical and behavioural pathologies.…”
Section: Early Experience and Neurobiological Developmentmentioning
confidence: 99%